2015
DOI: 10.1111/tri.12552
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation with deceased ABO-incompatible donors is life-saving but associated with increased risk of rejection and post-transplant complications

Abstract: SummaryABO-incompatible (ABOi) liver transplantation (LT) with deceased donor organs is performed occasionally when no ABO-compatible (ABOc) graft is available. From 1996 to 2011, 61 ABOi LTs were performed in Oslo and Gothenburg. Median patient age was 51 years (range 13-75); 33 patients were transplanted on urgent indications, 13 had malignancy-related indications, and eight received ABOi grafts for urgent retransplantations. Median donor age was 55 years (range 10-86). Forty-four patients received standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…In the LT literature, a 2012 retrospective study of the UNOS database of A2 → O ABO‐nonidentical LT showed that A2 → O mismatches to be safe with similar patient and graft survival to O → O ABO‐identical LT . The acceptability of A2 → O ABO‐incompatible transplantation has also been independently demonstrated in Europe and Asia . When we analyzed the distribution of A2 → O transplantation, we found significant regional variation with most of these operations taking place in regions 5 (23%), 2 (14%), 11 (13%), and 3 (10%).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In the LT literature, a 2012 retrospective study of the UNOS database of A2 → O ABO‐nonidentical LT showed that A2 → O mismatches to be safe with similar patient and graft survival to O → O ABO‐identical LT . The acceptability of A2 → O ABO‐incompatible transplantation has also been independently demonstrated in Europe and Asia . When we analyzed the distribution of A2 → O transplantation, we found significant regional variation with most of these operations taking place in regions 5 (23%), 2 (14%), 11 (13%), and 3 (10%).…”
Section: Discussionmentioning
confidence: 68%
“…LT. 22 The acceptability of A2 → O ABO-incompatible transplantation has also been independently demonstrated in Europe and Asia. [23][24][25] When we analyzed the distribution of A2 → O transplantation, we found significant regional variation with most of these operations taking place in regions 5 (23%), 2 (14%), 11 (13%), and 3 (10%). These This study has several limitations.…”
Section: Discussionmentioning
confidence: 94%
“…However, these patient survivals came at the price of a high rate of vascular and biliary complications and a high rate of retransplantations. The graft survivals of the A2 ABOin DDLT were slightly better (although statistically nonsignificant due to the small sample size) than the non-A2 ABOin DDLT (80% vs. 60% at 1 year and 67% vs. 48% at 3 years, respectively) [1].In contrast to other types of transplanted organs, the liver graft is somehow protected against preformed antibodies. It has been established for decades that liver transplantation against blood group is possible both in children and in adult recipients, with prolonged graft survivals without rejection in some cases [3].…”
mentioning
confidence: 78%
“…
In this issue of Transplant International, two separate groups, one from China and one from northern Europe, present their retrospective experiences and results in ABOincompatible (ABOin) deceased donor liver transplantation (DDLT) in adult recipients [1,2]. Both groups conclude that ABOin DDLT might be life-saving and might be used in urgent cases.In the study by the Sun Yat-sen University group from Guangzhou, China [2], in a population of recipients suffering from acute hepatitis B virus liver failure, ABOin graft survival was 28% at 3 years, compared with 66.5% and 71% for ABO compatible (ABOc) and ABO identical (ABOid) grafts, respectively (P < 0.05).
…”
mentioning
confidence: 99%
“…We assume that splenectomy or anti-CD20 treatment combined with PTP and reinforced immunosuppression can lead to over-immunosuppression and severe systemic infections [1,28]. In the study by Thorsen et al [17], 44 of 66 patients deceased after ABOi LDLT despite anti-CD20 administration. Most Asian centers use protocols with anti-CD20, plasmapheresis, intravenous immunoglobulin (IVIG), local graft perfusion, and splenectomy [23].…”
Section: Discussionmentioning
confidence: 99%